PENGARUH KEPEMILIKAN ASING, UKURAN PERUSAHAAN, BEBAN PAJAK DAN PERTUMBUHAN PENJUALAN TERHADAP TRANSFER PRICING - Angel Excellen Maharanihalim; Neneng Hasanah (Publika Citra Media, 2026)
This study aims to analyze the effect of Foreign Ownership, Company Size, Tax Burden and Sales Growth on Transfer Pricing in Food and Beverage companies. The data used are Food and Beverage companies listed on the Indonesia Stock Exchange for the 2019-2023 period. The sample determination uses a purposive sampling method. The sample in this study was 12 for 5 years, resulting in 60 data. The analysis method of this study uses multiple linear regression methods to test the effect of tax burden, foreign ownership, and company size on the dependent variable transfer pricing. Based on the results of statistical calculations, it was concluded that (1) The results of the simultaneous test (F) show that Foreign Ownership, Company Size, Tax Burden and Sales Growth together have an effect on Transfer Pricing, (2) The results of the partial test (t) Foreign Ownership and Company Size have an effect on Transfer Pricing, (3) The results of the partial test (t) Tax Burden and Sales Growth have no effect on Transfer Pricing.